Advances in Leishmania Research: From Basic Parasite Biology to Disease Control - Nuno Santarém; Luís Cardoso; Anabela Cordeiro-da-Silva (Microorganisms, 2023)
The genus Leishmania (Trypanosomatida: Trypanosomatidae) currently comprises just over 50 species, of which about 20 cause several syndromes in humans, collectively known as leishmaniasis or “leishmaniases” [...]